(untitled) - International Rice Research Institute (Los Banos, Philippines, 1978)
The book musters the knowledge for wetland soils on which rice is grown and discusses the relevance of that information to rice production. Ninety-three soil and plant scientists from 23 countries gathered to discuss subjects that covered the distribution, pedology, physics, chemistry, electrochemistry, microbiology, fertility, management, and nutritional problems of wetland rice soils
Keywords: Rice,Soil science; Soils